Becoming-design in corresponding: re/theorising the co- in codesigning. Issue 1 (2nd January 2017) - Roth, Wolff-Michael; Socha, David; Tenenberg, Josh
Abstract: Co designing tends to be identified with co llaborative endeavours to produce designs. In this study, grounded in an anthropology of making, we propose a radically different use of the 'co-' that emphasises the continued becoming and mutual shaping of people-and-materials-becoming-design. An extended case study of a design critique presentation from a graduate course in industrial design is used to exemplify this different perspective. It expands upon the common use of the understanding of codesigning by bringing to the fore not only the back-and-forth movement of people and evolving designs in correspondence with each other but also the transverse movement, which is the intertwining streams of perduring life. Codesign is thus understood as a process of designer, materials and designed objects coming into co rrespondence while co rresponding (conversing) with each other, and all designing is understood as codesigning The approach decentres common agent-centred notions of designing to focus on the continued becoming-design that shapes designers and their materials alike.